Recent insights into the functions and mechanisms of antisense RNA: emerging applications in cancer therapy and precision medicine - Rehman, Shahab Ur; Ullah, Numan; Zhang, Zhenbin; Zhen, Yongkang; Din, Aziz-Ud; Cui, Hengmi; Wang, Mengzhi (Frontiers in Chemistry, 2024)
The antisense RNA molecule is a unique DNA transcript consisting of 19-23 nucleotides, characterized by its complementary nature to mRNA. These antisense RNAs play a crucial role in regulating gene expression at various stages, including replication, transcription, and translation. Additionally, artificial antisense RNAs have demonstrated their ability to effectively modulate gene expression in host cells. Consequently, there has been a substantial increase in research dedicated to investigating the roles of antisense RNAs. These molecules have been found to be influential in various cellular processes, such as X-chromosome inactivation and imprinted silencing in healthy cells. However, it is important to recognize that in cancer cells;, aberrantly expressed antisense RNAs can trigger the epigenetic silencing of tumor suppressor genes. Moreover, the presence of deletion-induced aberrant antisense RNAs can lead to the development of diseases through epigenetic silencing. One area of drug development worth mentioning is antisense oligonucleotides (ASOs), and a prime example of an oncogenic trans-acting long noncoding RNA (lncRNA) is HOTAIR (HOX transcript antisense RNA). NATs (noncoding antisense transcripts) are dysregulated in many cancers, and researchers are just beginning to unravel their roles as crucial regulators of cancer's hallmarks, as well as their potential for cancer therapy. In this review, we summarize the emerging roles and mechanisms of antisense RNA and explore their application in cancer therapy.